Osteoarthritis and the Tactical Athlete: A Systematic Review - Cameron, Kenneth L. (J Athl Train, 2016)
OBJECTIVE: Although tactical athletes (eg, military service members, law enforcement personnel, fire fighters) are exposed to several known risk factors, it remains unclear if they are at increased risk for osteoarthritis (OA). The purpose of this systematic review was to investigate the association between serving as a tactical athlete and the incidence and prevalence of OA. DATA SOURCES: We completed a comprehensive systematic literature search in November 2014 using 12 bibliographic databases (eg, PubMed, Ovid, SportDiscus) supplemented with manual searches of reference lists. STUDY SELECTION: Studies were included if they met the following criteria: (1) an aim of the study was to investigate an association between tactical athletes and OA; (2) the outcome measure was radiographic OA, clinical OA, total joint replacement, self-reported diagnosis of OA, or placement on a waiting list for a total joint replacement; (3) the study design was a cohort study; and (4) the study was written in English. DATA EXTRACTION: One investigator extracted data from articles that met all inclusion criteria (eg, group descriptions, measures of disease burden, source of nonexposed controls). DATA SYNTHESIS: Twelve articles met the inclusion criteria and described retrospective cohort studies. Firefighters, active-duty military service members, and veteran military parachutists consistently had a higher incidence or prevalence of knee, hip, or any OA diagnosis (4 studies). Active-duty pilots and veteran military parachutists may have a higher prevalence of spine OA, but this was not statistically significant (2 studies). Occupational risk factors for OA among tactical athletes include rank and branch of military service. The risk of OA among individuals who completed mandatory national military service remains unclear (6 studies). CONCLUSIONS: The incidence of OA among tactical athletes appears to be significantly higher when compared with nonexposed controls. Further research is needed to specifically identify modifiable risk factors within this high-risk population to develop and implement effective risk-reduction strategies.